2020
DOI: 10.3390/ani10010107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Added Dietary Fiber and Rearing System on the Gut Microbial Diversity and Gut Health of Chickens

Abstract: It is of merit to study the appropriate amount of dietary fiber to add to free-range chickens’ feed to improve their microbial diversity and gut health in times of plant fiber deprivation. Lignocellulose is a useful source of dietary fiber, and its positive effects on the growth performance and laying performance of chickens has already been proven. However, few researchers have researched the effects of adding it on the gut microbiota of chickens. In this research, we added three different levels of eubiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
(62 reference statements)
0
23
1
Order By: Relevance
“…Moreover, increasing concentrations of dietary LC decreased counts of Escherichia/Hafnia/Shigella [ 25 ]. Four recent studies using a potential more fermentable LC product also displayed conflicting results regarding the effect of dietary LC on the gut microbiota in broilers and laying hens [ 22 , 24 , 35 , 86 ]. The feeding of isoenergetic, isonitrogenous diets containing 2% and 4% LC increased the cecal microbial diversity and the abundance of butyrate-producing bacteria in free-range chickens, while the luminal concentration of butyrate, acetate and propionate was not affected [ 86 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, increasing concentrations of dietary LC decreased counts of Escherichia/Hafnia/Shigella [ 25 ]. Four recent studies using a potential more fermentable LC product also displayed conflicting results regarding the effect of dietary LC on the gut microbiota in broilers and laying hens [ 22 , 24 , 35 , 86 ]. The feeding of isoenergetic, isonitrogenous diets containing 2% and 4% LC increased the cecal microbial diversity and the abundance of butyrate-producing bacteria in free-range chickens, while the luminal concentration of butyrate, acetate and propionate was not affected [ 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four recent studies using a potential more fermentable LC product also displayed conflicting results regarding the effect of dietary LC on the gut microbiota in broilers and laying hens [ 22 , 24 , 35 , 86 ]. The feeding of isoenergetic, isonitrogenous diets containing 2% and 4% LC increased the cecal microbial diversity and the abundance of butyrate-producing bacteria in free-range chickens, while the luminal concentration of butyrate, acetate and propionate was not affected [ 86 ]. In contrast, broilers and laying hens fed diets which were supplemented with 0.8% and 1% LC, showed no alterations in the overall cecal microbial diversity [ 22 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2016) found that the changes of fermentation of end products are likely to be associated with the density of the resident bacteria, and the cecum has greatest taxonomic diversity and abundance in the present study, which were in agreement with the previous studies ( Gong et al., 2007 ; Choi et al., 2014 ). In addition, the diet composition and rearing system are also the important influences of bacteria in the gut, and thus, SCFAs will change as diet component or rearing system varies ( Heinritz et al., 2016 ; Hou et al., 2020 ). Therefore, the effects of other types of diets or rearing system on gut microbiota, SCFAs, and intestinal morphology of broilers need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Other plant constituents contribute to influencing the microbiome and it is known that indigestible dietary fibers such as lignin can change the microbial composition (Hou et al 2020).…”
Section: Natural Products and Plant Extracts Against Campylobactermentioning
confidence: 99%